Diazaoxatriangulenium: synthesis of reactive derivatives and conjugation to bovine serum albumin. Issue 3 (3rd December 2015) - Bora, Ilkay; Bogh, Sidsel A.; Rosenberg, Martin; Santella, Marco; Sørensen, Thomas Just; Laursen, Bo W.
Abstract : The red emitting, long fluorescence lifetime diazaoxatriangulenium dye DAOTA has been prepared with reactive NHS-ester and maleimide linkers for bioconjugation. Abstract : The azaoxa-triangulenium dyes are characterised by emission in the red and a long fluorescence lifetime (up to 25 ns). These properties have been widely explored for the azadioxatrianguelnium (ADOTA) dye. Here, the syntheses of reactive maleimide and NHS-ester forms of the diazaoxatriangulenium (DAOTA) system are reported. The DAOTA fluorophore was conjugated to bovine serum albumin (BSA) and investigated in comparison to the corresponding ADOTA-BSA conjugate. It was found that the fluorescence of DAOTA experienced a significantly higher degree of solvent quenching if compared to ADOTA as non-conjugated dyes in aqueous solution, while the fluorescence quenching observed upon conjugation to BSA was significantly reduced for DAOTA when compared to ADOTA. The differences in observed quenching for the conjugates can be explained by the different electronic structures of the dyes, which renders DAOTA significantly less prone to reductive photoinduced electron transfer (PET) quenching from e.g. tryptophan. We conclude that DAOTA, with emission in the red and inherent resistance to PET quenching, is an ideal platform for the development of long fluorescence lifetime probes for time-resolved imaging and fluorescence polarisation assay.